Outsourcing as a production model and customer loyalty of a financial company - Barra Solano, Morelia Magaly (2023)
Fil: Barra Solano, Morelia Magaly. Universidad Peruana Los Andes. Facultad de Ciencias Administrativas y Contables; Perú.